An analysis of financial performance of Liga Cempaka Sdn Bhd: using financial ratio analysis, common size Analysis and Comparative Analysis / Nur Hazwani Hashim - Hashim, Nur Hazwani (FACULTY OF BUSINESS MANAGEMENT, 2012)
Financial statement analysis is a part of business analysis. This paper analyzes the financial performance of Liga Cempaka Sdn Bhd from 2005 to 2009. To analyze the data researcher used three tools of financial analysis which are ratio analysis, common size and comparative analysis to see financial performance of the company. By using ratio analysis, researcher detect which is this company is good in term of liquidity but in term of leverage ratio company it is a highly depend on debt. For the activity ratio researcher find out which is this company is not efficient in term of collecting their debt and because of the problem, company also did not pay the debt on time follow the credit policy. In profitability ratio, this company is poor in earn the big profit and company need fix it to increase their income. Common size analysis is one tool to measure financial performance and after calculated it researcher find out this company is has high current assets than fixed assets. It is well for the company to meet short term obligation and this company has more liabilities than equities. For the overall performance of the common size analysis income statement is worse for the company because the graph shows more on decreasing trend. The Last tool that researcher used is comparative analysis. The conclusion of the comparative analysis balance sheet analysis in term of total asset, it give the good sign because from 100% in 2005 there are has increment in 2006 to 2009. For total debt of this company it is decrease and total equity of the company is has increment in 2007 and 2008 and unfortunately in 2009 total equity of the company decrease. For the income statement, overall performance of trend index analysis income statement is worst because showing decline. Researcher hope this study will assist Liga Cempaka Sdn Bhd to improve their financial performance after know the several problems and several recommendation.